Eating Disorders: An Evolutionary Psychoneuroimmunological Approach - Rantala, Markus J.; Luoto, Severi; Krama, Tatjana; Krams, Indrikis (Frontiers in Psychology, 2019)
Eating disorders are evolutionarily novel conditions that lead to some of the highest mortality rates of all psychiatric disorders. Several evolutionary hypotheses have been proposed for eating disorders, but only the intrasexual competition hypothesis is extensively supported by evidence. We present the mismatch hypothesis as a necessary extension to the current theoretical framework of eating disorders. This hypothesis explains the evolutionarily novel adaptive metaproblem that has arisen when mating motives and readily available food rewards conflict with one another. This situation is exacerbated in contemporary environments characterized by sedentary lifestyles, caloric surplus and the ubiquity of social comparisons that take place via social media. Our psychoneuroimmunological model connects ultimate-level causation with proximate mechanisms by showing how the adaptive metaproblem between mating motives and food rewards leads to chronic stress and, further, to disordered eating. Chronic stress causes neuroinflammation, which increases susceptibility to OCD-like behaviors that typically co-occur with eating disorders. Chronic stress upregulates the serotonergic system and causes dysphoric mood in patients with restricting-type anorexia nervosa. Dieting, however, reduces serotonin levels and dysphoric mood, leading to a vicious serotonergic-homeostatic stress/starvation cycle whereby cortisol and neuroinflammation increase through stringent dieting. Between-individual and within-individual variation in eating disorders partially arises from (co)variation in gut microbiota and stress responsivity, which influence neuroinflammation and the serotonergic system. In binge-related eating disorders, even a short period of fasting drops serotonin levels, a state alleviated by binge eating. Eating disorder treatments should aim to reduce the chronic stress, neuroinflammation, stress responsivity and gut dysbiosis that fuel the disorders. We review the advances that have been made in recent years in understanding how to best treat eating disorders, outlining directions for future clinical research. Connecting ultimate causes with proximate mechanisms and treating biopsychosocial causes rather than manifest symptoms will enable more effective and sophisticated long-term interventions for the millions of people who suffer from eating disorders.